THE INFLUENCES OF LIQUIDITY, PROFITABILITY, AND SOLVABILITY TO THE STOCK RISK IN MANUFACTURER COMPANIES LISTED IN BEI 2014-2016 - B1034131014, Tan Rizky Raya (Jurnal Kajian Ilmiah Akuntansi Fakultas Ekonomi UNTAN (KIAFE), 2018)
Risks are caused by uncertainty about profits or expected feedback or what you want to get. For this reason, every time a decision is made to invest, an investor must at least consider two things, namely the expected return and risk contained in the investment alternative that he does. This is important to consider because investments are planted usually in large quantities. The population in this study is the data of manufacturing companies listed on the Stock Exchange in 2014-2016. The sample of this study amounted to 30 companies using purposive sampling method. This study uses a classical assumption regression, to determine the variables that affect stock risk. The results of this study indicate that there are three variables that significantly influence the risk of shares. Variable profitability, solvency and liquidity. Profitability has a positive effect on stock risk. Whereas solvency and liquidity negatively affect the risk of shares.Andayani, Tutut Dwi. 2010. Skripsi. Pengaruh Karakteristik Dewan Komisaris Independen Terhadap Manajemen Laba. Universitas Diponegoro. Semarang.Augusty, Ferdinand. 2006. Metode Penelitian Manajemen: Pedoman Penelitian untuk skripsi, Tesis dan Disertai Ilmu Manajemen. Semarang: Universitas Diponegoro.Â Brigham, Eugene F dan Houston. 2006.Â Fundamental of FinancialManagement: Dasar-Dasar Manajemen Keuangan.Â Edisi 10. Jakarta: Salemba Empat.Â Deswira, 2009.Â Pengaruh Likuiditas, Struktur Modal dan Ukuran Perusahaan Terhadap Resiko Investasi Saham yang Terdaftar di Jakarta Islamic Index.Â Universitas Negeri Padang uploaded onÂ http://ejournal.unp.ac.idDjarwanto PS, dan Subagyo, Pangestu. 2005. Statistik Induktif. Edisi Kelima. Yogyakarta : BPFE.Djayani Nurdin, 1994,Â Analisis Kinerja Keuangan sebelum dan sesudah akuisisi pada Perusahaan Go Public di Indonesia, siasat Bisnis,Â TH.1, Vol 3Ghozali, Imam. 2006. Aplikasi Analisis Multivariate dengan Program SPSS. Edisi Kedua. Yogyakarta. Penerbit Universitas Diponegoro.Jack Clark Francis dalam salah satu bukunya yaitu Investment: Analysis and Management, 5th edition, McGraw-Hill Inc., Singapore, 1991, Hal. 1Â Jensen, M.C. dan W.H. Meckling. 1976.Â Theory of The Firm : Managerial Behaviour, Agency Cost and Ownership Structure.Â Journal of Financial EconomicÂ 3.Jiraporn, Pornsit, Pandej Chintrakarn dan Yixin Liu. "Capital Structure, CEO Dominance and Corporate Performance." Journal Financial Service Research, 2012, hal: 139-158.Jogiyanto, H.M, 2010.Â Teori Portofolio dan Analisis Investasi.Â Edisi Ketujuh. BPFE, YogyakartaGitman,Lawrance.J, 2003.Â Principle of Managerial Finance, Ten edition, Pearson education, inc.,United statesHarahap, Sofyan Syafri. 2009. â€œAnalisis Kritis Atas Laporan Keuanganâ€. Jakarta: RajaGrafindo PersadaHusnan, Suad, 1998.Â Dasar-dasar Teori Portofolio dan Analisis Sekuritas,Â 2ndEdition, Yogyakarta : UPP-AMP YKPNSefiana, E. 2009. Pengaruh Penerapan Corporate Governance terhadap Manajemen Laba pada Perusahaan Perbankan yang Telah Go Publik di BEI. Jurnal Ekonomi Bisnis dan Akuntansi Ventura 12(3):211-222.Sidauruk, 2015.Â Pengaruh Liquidity, Leverage, Profitability, Firm SizeDan Sales Growth Terhadap Risiko Saham.Â Universitas Diponegoro, Semarang.Â Sudiyatno dan Nuswhadari.2009. Peran Beberapa Indikator Ekonomi Dalam Mempengaruhi Risiko Sistematis Perusahaan Manufaktur di Bursa Efek Indonesia Jakarta.Â Jurnal Dinamika Keuangan dan Perbankan, Vol. 1No.2.Sumarno, 2014.Â Pengertian Risiko.Â Uploaded on 14thof February 2018,Â https://es.scribd.com/document/267027744/PENGERTIAN-RISIKOTandelilin, Enduras. 2010.Â Analisis Investasi dan Manajemen Portofolio.Â Edisi 1. Yogyakarta: Kanisius.Weston, J. Fred, dan Copeland, Thomas E., (1992),Â Managerial Finance, 9thedition, The Dryden Press, A Harcourt Brace Jovanovic College Publisher, USA, Canada, Tokyo, etc.Â